2021
DOI: 10.3389/fonc.2021.637420
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Cancer Vaccination With a Peptide Derived From the Calreticulin Exon 9 Mutations Induces Strong Cellular Immune Responses in Patients With CALR-Mutant Chronic Myeloproliferative Neoplasms

Abstract: BackgroundThe calreticulin (CALR) exon 9 mutations that are identified in 20% of patients with Philadelphia chromosome negative chronic myeloproliferative neoplasms (MPN) generate immunogenic antigens. Thus, therapeutic cancer vaccination against mutant CALR could be a new treatment modality in CALR-mutant MPN.MethodsThe safety and efficacy of vaccination with the peptide CALRLong36 derived from the CALR exon 9 mutations was tested in a phase I clinical vaccination trial with montanide as adjuvant. Ten patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 103 publications
2
33
0
Order By: Relevance
“…Although a decline in platelet count was observed in the initial 100‐day period after vaccination, unfortunately none of the patients had either a clinical or molecular response. In this study, IFNγ enzyme‐linked immunospot (ELISPOT) responses were observed in four of 10 patients before vaccination, and in four additional patients after vaccination, confirming an increase in in vitro anti‐cancer immune activity and a potential role for therapeutic vaccines combined with other modalities to enhance the efficacy of anti‐tumour T‐cell activity 88 …”
Section: The Role Of Innate and Adaptive Immunity In Myeloproliferati...supporting
confidence: 59%
See 1 more Smart Citation
“…Although a decline in platelet count was observed in the initial 100‐day period after vaccination, unfortunately none of the patients had either a clinical or molecular response. In this study, IFNγ enzyme‐linked immunospot (ELISPOT) responses were observed in four of 10 patients before vaccination, and in four additional patients after vaccination, confirming an increase in in vitro anti‐cancer immune activity and a potential role for therapeutic vaccines combined with other modalities to enhance the efficacy of anti‐tumour T‐cell activity 88 …”
Section: The Role Of Innate and Adaptive Immunity In Myeloproliferati...supporting
confidence: 59%
“…The safety and efficacy of vaccination with a peptide derived from the CALR exon 9 mutation was recently tested in a phase I clinical trial in 10 patients with mut CALR MPN 88 . Although a decline in platelet count was observed in the initial 100‐day period after vaccination, unfortunately none of the patients had either a clinical or molecular response.…”
Section: The Role Of Innate and Adaptive Immunity In Myeloproliferati...mentioning
confidence: 99%
“… 17,30 Similarly, in a recent phase 1 study that evaluated the safety and efficacy of vaccination against mutated CALR in patients with MPNs, vaccine-induced T-cell responses were significantly greater in patients with essential thrombocythemia than in those with MF. 31 Of note, although this study demonstrated safety and tolerability, the mutated CALR vaccine had no clinical efficacy. 31 Taken together, these findings underscore the multifactorial causes of immune tolerance in MPNs.…”
Section: Discussionmentioning
confidence: 75%
“… 31 Of note, although this study demonstrated safety and tolerability, the mutated CALR vaccine had no clinical efficacy. 31 Taken together, these findings underscore the multifactorial causes of immune tolerance in MPNs. These observations also suggest that as disease progresses, a coordinated dysregulation of the immune milieu may contribute to antitumor T-cell suppression.…”
Section: Discussionmentioning
confidence: 75%
“…Therapeutic cancer vaccination against mutated CALR was suggested as a new treatment modality in CALR-mutated MPN. Although many patients displayed T cell responses, unfortunately, no clinical responses have been observed so far [ 97 ].…”
Section: Novel Therapeutics Targeting Mpn Progressionmentioning
confidence: 99%